Core chemotype diversification in the HIV-1 entry inhibitor class using field-based bioisosteric replacement. Issue 1 (1st January 2016) - Tuyishime, Marina; Lawrence, Rae; Cocklin, Simon
Graphical abstract: Abstract: Demand remains for new inhibitors of HIV-1 replication and the inhibition of HIV-1 entry is an extremely attractive therapeutic approach. Using field-based bioisosteric replacements, we have further extended the chemotypes available for development in the HIV-1 entry inhibitor class. Moreover, using field-based disparity analysis of the compounds, 3D structure–activity relationships were derived that will be useful in the further development of these inhibitors towards clinical utility.